IMPACT OF MATERNAL PROFILE ON BIRTH OUTCOMES - Gracimary Alves Teixeira; Jovanka Bittencourt Leite de Carvalho; Brismark Góes da Rocha; Silvana Alves Pereira; Bertha Cruz Enders (Universidade Federal do Paraná, 2018)
Objective: to identify the impact of maternal profile on birth outcomes. Method: Descriptive cross-sectional study with a sample of 244 postpartum women, as follows: 109 mothers of preterm infants and 135 mothers of full-term infants. The births occurred in the April-September 2015 period in a public maternity hospital in the Northeastern region of Brazil. Data was analyzed with Statistica 10 software and Chi-square test. Results: high prevalence of sedentary lifestyle; statistical significance for overweight and obesity before and during pregnancy; high prevalence of high blood pressure during the gestational period of mothers of preterm infants. Also, 58.1% (n = 63) of preterm infants were born with health problems and 96.3% (n = 130) of full-term infants were healthy. Conclusion: Maternal obesity and overweight is a risk factor for preterm births, an event that demands child healthcare.